The value of network information - Itay P. Fainmesser; Andrea Galeotti (Brown University, Department of Economics, 2013)
The business model of companies such as Facebook, MySpace, and Twitter, relies on monetizing the information on the interactions and influences of their users. How valuable is such information, and is its use beneficial or detrimental for consumer welfare? We study these questions in a model where a monopoly sells a network good and may price discriminate using network information: information on consumers in uences and/or on consumers susceptibilities to in uence. Our framework incorporates a rich set of market products, including goods characterized by global and local network effects. We derive results on the value of network information and determine under which conditions, relative to uniform price, consumer surplus increases. We demonstrate the applicability of our framework using survey data on various types of relationships.
Keywords: 330